2013
DOI: 10.4308/hjb.20.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Amylase-Producing Bacillus spp. from “Tape” (Fermented Cassava)

Abstract: Fermented cassava or “Tape” is one of traditional Indonesian fermented food. The quality of “Tape” is determined by microorganisms involved during fermentation process. It was reported that Bacillus subtilis determined the quality of cassava “Tape”. The most common way to identify species is by using 16S rRNA gene. This gene contains conserved regions as unique sequence which is relative among species. It has been widely used as a reliable molecular marker for phylogeny identification. Therefore, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
8
0
3
Order By: Relevance
“…Yeasts are commonly present in many fermented foods [6,11,12,62] and starter culture [63]. Spore-forming bacteria could also be part of the microbial consortium in traditional Indonesian fermented foods, such as tempe [5] and tape [6,64] as well as their starter cultures [62].…”
Section: Potential Of Lactic Acid Bacteria Isolated From Indonesian Fmentioning
confidence: 99%
“…Yeasts are commonly present in many fermented foods [6,11,12,62] and starter culture [63]. Spore-forming bacteria could also be part of the microbial consortium in traditional Indonesian fermented foods, such as tempe [5] and tape [6,64] as well as their starter cultures [62].…”
Section: Potential Of Lactic Acid Bacteria Isolated From Indonesian Fmentioning
confidence: 99%
“…The other bacteria found in tape are Bacillus spp. (Barus et al, 2013). The LAB in commercial tape in Indonesia are between 10 6 -10 7 cfu/g, while AAB are between 10 5 -10 7 cfu/g.…”
Section: Introductionmentioning
confidence: 93%
“…can metabolize ethanol into acetic acid and can associate with yeast in alcohol fermentation (Nuraida and Owens, 2014). Barus et al (2013) reported the presence of 26 Bacillus spp. species contained in tape.…”
Section: Correlation Between Lactic Acid Bacteria Density and Sensorymentioning
confidence: 99%
See 1 more Smart Citation
“…Selanjutnya dilakukan ekstraksi dengan etil asetat untuk melihat senyawa apa yang dihasilkan oleh B. subtils B315 sebagai karakter aktivitas antibiosis (Kumar et al, 2009 Hasil perhitungan enzim amilase menunjukkan aktivitas sebesar 0,802 unit/ml setiap 30 menit dengan panjang gelombang 275 nm (Tabel 2). Menurut Barus et al (2013), Bacillus sp. menghasilkan amilase dari tape (fermentasi cassava) dengan aktivitas berkisar 4,8-29,1 unit/ml pada suhu 37 o C. Bacillus sp.…”
Section: Pengujian Penghambatan B Subtilis In Vitrounclassified